Bookstore's centralized approach of recording system (BCARS) / Norizan Mohd Saleh - Mohd Saleh, Norizan (1999)
This project develops a system to satisfy the needs of the management personnel of a bookstore and the end-users of the book lovers. It is known as Bookstore's Centralized Approach of Recording System (BCARS), which consists of three main sub-systems that are, the Book's Inventory sub-system. Search Engine sub-system and Sales/Rent sub-system. At the management personnel's side, the system consists of all the three sub-systems while at the customer's side, the system only consists of the search engine. The Book's Inventory and Sales/Rent sub-systems will assist the management personnel to keep a record of the collection of books such as the book's inventory and sales. Reports on sales and inventory can be viewed and printed for further analysis. This system can be extended by adding more tasks due to the changes required by the management personnel. The Search Engine sub-system will serve the customers in a more advanced searching method, based on the library OP AC system, despite of the traditional way of finding books through racks or shelves. The customers are no longer have to physically scanning through the books at the racks but just sitting at the computer terminal and start searching the materials they desired. All of the front covers of the books viewed will be displayed to the customers in order to help them to make wise decisions.